Proceedings of the 13th International Workshop on Semantic Evaluation 2019
DOI: 10.18653/v1/s19-2093
|View full text |Cite
|
Sign up to set email alerts
|

UTFPR at SemEval-2019 Task 5: Hate Speech Identification with Recurrent Neural Networks

Abstract: In this paper we revisit the problem of automatically identifying hate speech in posts from social media. We approach the task using a system based on minimalistic compositional Recurrent Neural Networks (RNN). We tested our approach on the SemEval-2019 Task 5: Multilingual Detection of Hate Speech Against Immigrants and Women in Twitter (HatEval) shared task dataset. The dataset made available by the HatEval organizers contained English and Spanish posts retrieved from Twitter annotated with respect to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Comparison with previous Results It is not straightforward to compare with previous results due to different data splits, or labeled tweets becoming unavailable over time. The best hate detection results on the SemEval (SE) dataset were reported to be 0.65 in macro-F1 (Paetzold et al, 2019). Our results are favorable, ranging from 0.68-0.80 in macro-F1.…”
Section: Cross-dataset Resultsmentioning
confidence: 47%
“…Comparison with previous Results It is not straightforward to compare with previous results due to different data splits, or labeled tweets becoming unavailable over time. The best hate detection results on the SemEval (SE) dataset were reported to be 0.65 in macro-F1 (Paetzold et al, 2019). Our results are favorable, ranging from 0.68-0.80 in macro-F1.…”
Section: Cross-dataset Resultsmentioning
confidence: 47%
“…Recurrent neural networks ( Paetzold, Zampieri & Malmasi, 2019 ) are a type of neural network in which the connections between nodes form a directed graph along a temporal sequence. Among the different variants of this type of network, the Long Short-Term Memory Network (LSTM) ( Talita & Wiguna, 2019 ; Bisht et al, 2020 ; Zhao et al, 2020 ; Zhang et al, 2021 ), which were specifically designed to avoid the problem of long-term dependency.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, in order to break the barrier of language dependency in word embedding approach, [19] conducted an ensemble of RNN classifiers, incorporating various features associated with user related information. [20] experimented with a robust system based on compositional RNNs able to handle even substantially noisy inputs, and reached competitive results for HS detection in English texts. In [21] authors developed a system for Twitter HS text identification based on two CNNs and feature embeddings including one-hot encoded character n-gram vectors and word embeddings, and they reported that the use of character n-gram does not help in the detection.…”
Section: Related Workmentioning
confidence: 99%